2012
DOI: 10.1016/j.virol.2011.11.025
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Oas1a gene expression by type I IFN requires both STAT1 and STAT2 while only STAT2 is required for Oas1b activation

Abstract: The murine 2′-5′ oligoadenylate synthetase 1a (Oas1a) and Oas1b genes are type 1 IFN responsive genes. Oas1a is an active synthetase with broad antiviral activity mediated through RNase L. Oas1b is inactive but can inhibit Oas1a synthetase activity and mediate a flavivirus-specific antiviral activity through an unknown RNase L-independent mechanism. Analysis of promoter elements regulating gene transcription confirmed that an IFN-stimulated response element (ISRE) is required for IFN beta-activation but neithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 75 publications
1
17
0
Order By: Relevance
“…3A, B and C). Consistent with previous observations (Ousman et al, 2005; Pulit-Penaloza et al, 2012), no upregulation of Oas1a after stimulation with IFN beta was observed in either tSTAT1−/− or tSTAT2−/− MEFs (Fig. 3A), while Oas1b (Fig.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…3A, B and C). Consistent with previous observations (Ousman et al, 2005; Pulit-Penaloza et al, 2012), no upregulation of Oas1a after stimulation with IFN beta was observed in either tSTAT1−/− or tSTAT2−/− MEFs (Fig. 3A), while Oas1b (Fig.…”
Section: Resultssupporting
confidence: 93%
“…The Oas1a and Oas1b promoters each contain a canonical ISRE (Pulit-Penaloza et al, 2012), Irf7 contains an inverted ISRE (Ning et al, 2005; Schmid et al, 2010) and the Irf1 promoter has a GAS element instead of an ISRE which is upregulated in IFN-stimulated cells by a STAT1 dimer (Pine et al, 1994). STAT1 and STAT2 occupancy on the Oas1a, Oas1b and Irf7 promoters and STAT1 occupancy on the Irf1 promoter in vivo was analyzed with a chromatin immunoprecipitation (ChIP) assay done as described in Materials and Methods using tC3H/He MEFs that were mock-infected, infected with WNV Eg101 (MOI of 5) for 7, 16 or 24 h or treated with 1000 U/ml of murine IFN beta for 30 m. Briefly, in vivo crosslinked DNA-protein complexes were immunoprecipitated using anti-STAT1, anti-STAT2 or a nonspecific IgG antibody.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Induction of mouse Oas1b and IRF7 by type I IFNs likewise has been described to be STAT1-independent. IFNβ induction of the Oas1b gene in Stat1(Δ1-124) −/− MEFs is STAT1-independent but STAT2-dependent (Pulit-Penaloza et al, 2012), and induction of IRF7 following lymphocytic choriomeningitis virus (LCMV) infection or IFNα treatment is STAT2- and IRF9-dependent but independent of STAT1 based on Stat1(Δ1-124) −/− knockout (Ousman et al, 2005). LCMV also has been seen to evade the mouse immune system through a type I IFN-mediated response that is STAT1-independent but STAT2-dependent (Hahm et al, 2005).…”
Section: Discussionmentioning
confidence: 99%